AUTISM AT EASE: AN ASSISTIVE TOOL FOR AUTISTIC CHILDREN - Vadamodula, Prasad; R, Priyavaijayanthi; Katta, Somesh (International Journal of Psychosocial Rehabilitation, 2020)
Autism Spectrum Disorder (ASD) is the widespread deficiency among the children, but now a days due to the development of sophisticated technologies a focus is made on the people who are suffering from autism and how to predict the same at earlier stages. So, based on the children’s mentality and their actions, the identification of the problem whether it is serious or normal is predicted. This project provides a feasibility to understand the current status of the patient from the information which is collected from their parents/guardians related with their social development, communication difficulties and weird behavior activities in the society. Further, the necessity learning is provided to enhance their mindsets with the planned activities. This project deals with a development of an android mobile application in regional language which is related to rectify the problems to limited extent by making their minds refresh by engaging them in online activities. This mobile application may help the parents, doctors to assist their children to some extent.